Pre-Service Science Teachers’ Skills to Express The Algorithms Used in Solving Physics Problems with Flowcharts (An Example From Turkey) - Kurt, H. S.; Doğan, Z. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
Due to the nature of physics, problem-solving strategies are applied in some cases to teach many subjects. Problem-solving is a process that individuals use, not only in physics classes but also in every stage of life. An algorithm is a pathway to solving a problem or achieving a specific purpose. The purpose of this study is to identify how pre-service science teachers express the algorithms they utilize in the process of solving physics problems. The research design of the study was determined as survey design which is one of the quantitative research methods. The study was carried out with the number of 34 pre-service science teachers consisting of 1st and 3rd-year university students who took General Physics I and General Physics Lab I courses in the undergraduate program in science education at a state university. They were given three problems regarding classical mechanics and then asked to solve these problems and schematize their algorithms by using flowcharts. The International System of Units (SI) was used throughout the research. An evaluation was made by comparing the 3 algorithms of the solution, whose reliability and validity was ensured, and which was previously created with the help of 3 experts. In the study, descriptive survey model was used. Frequency tables were frequently used in the analysis of the data with the intent to present the study in the best way by doing an in-depth analysis. In the findings of the research, it was observed that pre-service science teachers had problems in expressing their algorithms and some of them could not express these algorithms at all. It was also observed that pre-service science teachers had difficulty describing the solutions they created while setting up the problem. However, it was observed that preservice science teachers who could illustrate their algorithms well were usually the ones who solved the problems correctly.